Production of Surface Layer with Gradient Microstructure and Microhardess on Copper by High Pressure Surface Rolling - Juying Li; Qingsong Mei; Yana Li; Beihai Wang (Metals, 2020)
Pure copper was subjected to high-pressure surface rolling (HPSR) to obtain a surface gradient layer. Effects of HPSR parameters on the surface microstructure and microhardness of Cu were investigated by using optical microscopy, transmission electronic microscopy, X-ray diffraction, and the microhardness test. The HPSR surface layer has a gradient microstructure consisting of increasingly refined grains with decreasing depth from the treated surface (DFS). The thicknesses of the refined surface layer can be up to ~1.8 mm, and the grain size of the topmost surface is down to ~88 nm, depending on the HPSR parameters including pressure, time, and temperature. Microhardness of HPSR samples increases with decreasing DFS, with a maximum of ~2.4 times that of the undeformed matrix. The present results indicated that HPSR could be an effective method for the production of a mm-thick surface layer on Cu with gradient microstructure and property.